SIMULASI IDENTIFIKASI DAERAH CODING PADA DEOXYRIBONUCLEIC ACID DENGAN MENGGUNAKAN DISCRETE FOURIER TRANSFORM - Agoes, Suhartati; Suryadi, Suryadi (Jurnal Teknik Elektro, 2005)
Deoxyribonucleic acid (DNA) is a genetic substance that brings heredity factor. DNA consistof four bases, which are adenine, timine, guanine, and citosine. Each base is symbolized byA, T, G, and C. There are coding and noncoding regions in DNA data. Coding region (calledexon) is a DNA region thatâs useful to describe heredity factor. Many methods can be used todetermine coding region in DNA data, one of them is by using Discrete Fourier Transform(DFT). Simulation using DFT is performed by entering the algoritm similarities into Matlablanguage program. The purpose of simulation are to predict exon length, to get the value ofoptimized spectral and to get the value of exon total power spectral. Optimized spectral isuseful to identify exon position in DNA data. The results of simulation reveal that the totalpower spectral value of exon is proportional to N-point DFT value for each DNA sequenceand the optimized spectral value of DNA is also proportional to quantity of exon bases andexon length. Optimized spectral value reaches maximum for more quantity of exon bases andmore length of exon than when optimized spectral value reaches minimum.Keywords: deoxyribonucleic acid, exon, optimized spectral, total power spectral.